Male outmigration, intra-household decision-making and agricultural production: the case of Nepal - Slavchevska, Vanya (International Center for Tropical Agriculture, 2019)
Presented by Vanya Slavchevska (CIAT), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.